TARİHSEL VE TEOLOJİK AÇILARDAN KADININ ÖRTÜNMESİ SORUNU - Bedriye Özçelik Yılmaz (İslami İlimler Dergisi)
The tradition of woman’s veiling including headscarf bases upon along history. In ancient civilizations, for example in Middle Assyria, a written law was in force that oblige free woman to veil and slaves to unveil. Jewish and Christian tradition has followed similar practices. Additively Woman’s veiling has symbolized the obedience to God and man in Christian tradition. According to statements of Quran, woman who have to be veiled is free women and Quran does not assign an additive meaning to veiling such as obedience to man. Headscarf, symbolizes that a women is free (esteemed) and gives her a social statue and implies her privacy.